Pengaruh Jalur Pelaporan dan Power Distance Terhadap Niat Melakukan Whistleblowing - Annisa Annisa; Sany Dwita (Universitas Negeri Padang, 2020)
This paper aims at examining the effect of wrongdoing reporting channels (anonymous and non-anonymous). Intention to report fraud via anonymous reporting channel are hypothesized to be higher than through non-anonymous reporting channel. As Hoftsede research of Indonesian culture, Indonesia has high score (78) on power distance dimention. This research uses experimental method to 152 students of Undergraduate of Accounting in UNP. By using eight-case scenarios, partispants were asked to answer the possibility to whistleblow the unethical behavior that occurred in the organization which was done by their manager or peer. The intention to report fraud via anonymous reporting channel is higher rather than via non-anonymous reporting channel. We also find that low power distance has positif impact for whistleblowing decision. Taken together, these findings contribute to the exising literature on accounting ethics.